ANALYSIS OF COMPLIANCE OF EAR PROTECTOR USAGE ON THE PREVENTION OF NOISE INDUCE HEARING LOSS AT STERILIZATION INSTALLATION - Rahmawati, Rosydiah; Purnami, Nyilo; Cahyani, Makhmudyah Indri (Journal of Community Medicine and Public Health Research, 2021)
Noise Induce Hearing Loss (NIHL) is a work disease that is often found in industrial workers. The use of ear protectors that are in accordance with the standard along with the continuity of optimal use can reduce the risk of hearing loss due to noise in the workplace. Adherence to use ear protectors greatly affect the possibility of a person experiencing a more severe hearing loss. The purpose of this study is to prove the existence of relationship of compliance with the use of ear protectors with hearing loss due to noise in the installation of sterilization and laundry. This study used cross sectional methods. Seventeen samples were taken by consecutive sampling for audiometry examination and measurement of compliance with the use of Ear Protective Equipment. Respondents received an average score of 1.86 indicating that compliance with the use of ear protectors was sufficient. Based on the results of the measurement of the auditory threshold in 17 respondents as many as 4 respondents (23%) normal hearing and as many as 13 respondents (77%) experienced NIHL. The results of statistical tests with Pearson correlation show that the Pearson correlation coefficient number of -0.643, which means that the correlation between compliance variables with noise due to noise is 0.643. Based on the criteria above, the relationship between the two variables is significant because the number of significance is P-value / Sig 0.005 <0.05. So, there is a relation between years of work with Noise Induce Hearing Loss, education and Noise Induce Hearing Loss, and compliance with the use of ear protectors with NIHL